Common law tracing: the Emperor’s new clothes? - Hafeez-Baig, MJ; English, JE (LexisNexis, 2018)
At the heart of the case for the unification of common law and equitable tracing rules is an assumption, namely, that common law tracing rules exist and are separate from equitable tracing rules. In this article we challenge the correctness of that assumption in Australian law. We demonstrate that as a matter of authority and principle, tracing at common law is not, and has never been, possible. The erroneous assumption began with a misreading of Taylor v Plumer. English courts have since recognised this error but have held, in effect, that it is now too late to turn back. We show that Australian law has not yet taken this step and offer several reasons why it should not do so. The position that obtains is that there are only equitable tracing rules in Australian law. We demonstrate that these rules are sufficient, noting in particular that the equitable rules can support certain actions for money had and received (as demonstrated by Heperu Pty Ltd v Belle). The result is not a unification of tracing rules but rather the removal of a historical anomaly based upon an error.